Australian Muslims' orientations to secular society: Empirical exploration of theoretical classifications. (June 2014) - Dryzek, John S.; Kanra, Bora
This article applies Q methodology in order to explore Australian Muslims' orientations to the secular society in which they live. The analysis is guided by some theoretical claims that are made about the dispositions of Muslims who live in Western societies. While a simple 'closed' versus 'open' dichotomy has some plausibility, deeper investigation reveals four empirical types: respectively, semi-engaged, coexisting, assertively religious and untroubled participant. These four types vary in the same direction from the theoretical specification that informed the search for the type in question in a way that appears to reduce the tension between the type and the norms of secular society. Generalizations commonly made in both popular and scholarly discourse about the problematic character of Muslim orientations to secular society appear not to apply in Australia.